2011
DOI: 10.1080/08873267.2011.567132
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the psychological rewards of a wilderness experience: An interpretive phenomenological analysis.

Abstract: This study was concerned with the subjective experiences of five women (N ¼ 5) on a 10-day Scottish wilderness trip focussing on well-being and environmental perceptions. Semistructured interviews, using an ethnographic approach, were subjected to interpretative phenomenological analysis (Smith, Jarman, & Osborn, 1999). The group shared common positive experiences characterized by feelings of connection, aliveness, contemplativeness, self-discovery, confidence, and well-being, although some deeper emotional ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…Supporting the findings of the present study, mindfulness has been found to be reactive in earlier studies; levels of mindfulness, as measured by the Freiburg Mindfulness Inventory (used in the present study), increased after a mindfulness retreat (Walach et al, 2006). Hinds (2011) writes that wonderment with the environment potentially has similar effects to mindfulness, while Unsworth et al (in press) found that nature contact was most effective when participants were instructed to conduct mindful meditation. RYL participants were not explicitly given instructions to be mindful but were encouraged to pay attention in ways they normally would not: instructions that may also be given during mindfulness practice.…”
Section: Discussionsupporting
confidence: 87%
“…Supporting the findings of the present study, mindfulness has been found to be reactive in earlier studies; levels of mindfulness, as measured by the Freiburg Mindfulness Inventory (used in the present study), increased after a mindfulness retreat (Walach et al, 2006). Hinds (2011) writes that wonderment with the environment potentially has similar effects to mindfulness, while Unsworth et al (in press) found that nature contact was most effective when participants were instructed to conduct mindful meditation. RYL participants were not explicitly given instructions to be mindful but were encouraged to pay attention in ways they normally would not: instructions that may also be given during mindfulness practice.…”
Section: Discussionsupporting
confidence: 87%
“…Hinds (2011), for this is where the individual can be free of the distractions of modern living and the senses can attend to the natural world. Hinds and Sparks (2011) found that wild landscapes were associated with greater "Eudemonia" than more managed landscapes, such as farmland.…”
Section: Mindfulness In Naturementioning
confidence: 99%
“…Hinds, 2011). This could have implications for communities who live in semi-rural and urban fringe areas with easy access to the countryside as it suggests that fulfilling and enriching experiences can be found on their doorstep with regular short exposure.…”
Section: Theme 2: Manifestations Of the Changementioning
confidence: 99%
“…Ecopsychological studies that explore the effects of direct experience on participant awareness focus mostly on environmental identity (ecologic self), affective connections and the sense of well-being that is often fostered (Hinds and Sparks 2009). Although there is a dearth of ecopsychology research about increasing awareness of the physical and biological aspects of the non-human world, many studies document both changes in 295 affective and spiritual responses and the development of a sense of place (the effect on the psyche) (Roszak 1995;Davis 1998;Harper, Carpenter et al 2011;Hinds 2011;Snell and Simmonds 2012). These aspects of direct experience are discussed in the "sense of connection" section of the discussion.…”
Section: Through Direct Experiencementioning
confidence: 99%
“…Rader (2009) found that participants had an improved mood after time spent outside in a park setting (Rader 2009). Hinds (2011 found that participants on a wilderness excursion shared feelings of aliveness, contemplativeness, self-discovery, confidence, and wellbeing (Hinds 2011). These studies establish that nature experiences engender overwhelmingly positive emotional responses, and SUYO!…”
Section: Positive Emotionsmentioning
confidence: 99%